The Influence Of Islamic Leadership Principles Of Aqidah And Akhlaq And Its Effects On Islamic Leadership Behavior Among Malaysian Army Officers - Zainal Abidin Bin Mohammed Salleh
Leadership is an integral part of human life, especially in military organizations. Scholars on leadership have done many studies in terms of characteristics, principles, styles and behaviours. Many studies have been done based on the theories of western scholars, but lately, studies involving Islamic leadership have become increasingly prominent. Although the number of studies involving leadership based on Islamic principles is still minimal compared to Western leadership, scholars interested in studying and evaluating the effectiveness of leadership based on Islamic principles are increasing whether in politics, business, military and others. In this study, the researcher assessed the influence of Islamic leadership in terms of aqidah and akhlaq and its impact on leadership behaviour among Malaysian Army Officers. The study involved 169 Army Officers working at the Army Headquarters, Ministry of Defense Malaysia. The study results found that from the context of Islamic leadership principles, aqidah and morality are high and have a significant relationship with Islamic leadership behaviour among respondents. However, aqidah is seen to have a more substantial influence on the behaviour of Islamic leadership than akhlaq among the Army Officers involved in this study. Therefore, Army Officers should make the practice of Islamic leadership in line with the teachings brought by the Prophet Muhammad SAW. At the same time, the Armed Forces Religious Corps must play an essential role in educating and continuing to teach Islamic values in their organizations.